Sarawak Craft Council; Sustaining The Indigenous Craft Of Sarawak - Rahah, Hj. Hasan; Faridah, Sahari; Lucas, Terry (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The Sarawak Craft Council is an important institution to the indigenous people of Sarawak. Since 1957, its main objective was to substantiate the importance of preserving craft production of 25 different ethnic groups living together throughout Sarawak. Crafts produced here signify the rich tropical vegetation materials such as rattan , bamboo or pandanus which become scarce from years of cultivation for this purpose. As a result, the usage of substitute materials which are more durable or available such as plastic are favored for mass production. Though its function remains the same, the new appearances slowly eradicate the original motives and aesthetic value along with the authenticity of the craft that symbolize their ethnic identity. Realizing that, in order to sustain the production of crafts by indigenous people, not only do they need to be responsible for their inherited craftsman's skill and styles but also the means of providing raw materials in order to ensure that crafts produced by each indigenous group will remain authentic to their artistic designation. In recent years the Sarawak Craft Council has encompassed various programs that first and foremost, taught the indigenous people in village areas to provide themselves with raw materials rather than depending on what the forest can provide them, or buying expensive raw materials from outside the village. This paper will describe how the Sarawak Craft Council carried out its tasks in preserving Sarawak invaluable heritage and outlaying specific strategies to ensure a healthy and steadfast development of the local handicraft industry.